Interacting factors that contribute to reading difficulties among primary five pupils a study in Sekolah Kebangsaan Saint Francis Xavier, Seratau, Kuching, Sarawak/ Samen Sanggod @ Sanggon - Sanggod @ Sanggon, Samen (2004)
The purpose of this study is to investigate the interacting factor that contribute to reading difficulties in English among primary five pupils of Sekolah Kebangsaan Saint Francis Xavier, Seratau, Kuching. Four factors have been identified and explained accordingly based on the findings. A number of 20 respondents were involved in the study. In analyzing data from the study, the researcher uses frequency and percentage to explain the outcome of the study.